Analysis of Factors that Influence the Success of E-commerce Business in MSMEs in the Fashion Sector (Wordgroot Case Study, Bandung City) - Azzahro, Hanifa; Putra Pratama, Rafly (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This research aims to analyse the factors that influence the success of E-commerce businesses in micro, small and medium enterprises (MSMEs) in the fashion sector in the city of Bandung, with a case study on Wordgroot. Data was collected through interviews with 105 respondents using a 5 Likert scale-based questionnaire. The results of the analysis show that E-commerce has a positive and significant influence on the performance of MSMEs, which is explained by the R² value of 76.2%. E-commerce has been proven to increase operational efficiency, product validity and expand markets. This research identifies that digital literacy, product innovation and infrastructure support and government policies are important factors in ensuring the sustainability of digital-based businesses. Thus, adopting E-commerce is the main strategy for MSMEs to increase competitiveness in the modern era. Keywords: E-commerce, MSMEs, business performance, digitalization, fashion sector